ANALYSIS OF SOFTWARE DEVELOPER PERCEPTIONS TOWARDS THE SELECTION OF JAVASCRIPT FRAMEWORK IN BATAM CITY - Yefta Christian; Hengky Hengky (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Javascript Framework has been used by a lot of developer in Batam. There are many Javascript Framework with similar functionality. this research aims to find out the influence between performance expectancy, effort expectancy, social influence, and facilitating conditions on developer decision in using Javascript Framework. Our qualitative research have 30 respondent and our quantitative research have 359 respondent. This research used disproportionate random sampling and the method we used in this research is multiple regressions methods. The result of our hypothesis testing state that there is significant influence performance expectancy, effort expectancy, social influence, and facilitating condition to use behavior.